2014
DOI: 10.3892/mmr.2014.2160
|View full text |Cite
|
Sign up to set email alerts
|

Substituted 3-acyl-2-phenylamino-1,4-naphthoquinones intercalate into DNA and cause genotoxicity through the increased generation of reactive oxygen species culminating in cell death

Abstract: Naphthoquinones interact with biological systems by generating reactive oxygen species (ROS) that can damage cancer cells. The cytotoxicity and the antitumor activity of 3‑acyl‑2‑phenylamino‑1,4‑naphthoquinones (DPB1‑DPB9) were evaluated in the MCF7 human breast cancer cell line and in male Ehrlich tumor‑bearing Balb/c mice. DPB4 was the most cytotoxic derivative against MCF7 cells (EC50 15 µM) and DPB6 was the least cytotoxic one (EC50 56 µM). The 1,4‑naphthoquinone derivatives were able to cause DNA damage a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Then, half of each group was euthanized for the evaluation of the ascitic fluid. Tumor growth was determined using the following equation [20] : Inhibition of tumor growth (%)=100- [(variation in waist circumference of the treated group×100)/variation in waist circumference of the control group]. Mice (n=6) from each group were kept alive to determine survival time [21] , [22] .…”
Section: Methodsmentioning
confidence: 99%
“…Then, half of each group was euthanized for the evaluation of the ascitic fluid. Tumor growth was determined using the following equation [20] : Inhibition of tumor growth (%)=100- [(variation in waist circumference of the treated group×100)/variation in waist circumference of the control group]. Mice (n=6) from each group were kept alive to determine survival time [21] , [22] .…”
Section: Methodsmentioning
confidence: 99%
“…Cells were counted by a TC10 counter (BioRad, USA). Inhibition of tumor growth (ITG) was calculated with basis on abdominal circumference change (AC) using Equation 1 [18]:…”
Section: Evaluation Of Antitumor Activitymentioning
confidence: 99%
“…1,4-Naphthoquinone exhibits a variety of biological activities, and its superior anticancer activity has attracted widespread attention (14,15). Many 1,4-naphthoquinone derivatives (plumbagin, mitomycin and shikonin) have been demonstrated to strongly inhibit the proliferation and induce apoptosis in cancer cells, but most of the derivatives also cause adverse side effects in normal cells (16). Previous studies have demonstrated that different substituent structures enable naphthoquinone derivatives to have different biological activities (17,18).…”
Section: Introductionmentioning
confidence: 99%